ศักยภาพการสื่อความหมายทางการท่องเที่ยวชุมชน: ชุมชนบ้านร่องไฮ จังหวัดพะเยา: The Potentiality of Community Tourism Interpretation: Rong Hai Community, Phayao Province - Pakdeepinit, Prakobsiri (Asian Health, Science and Technology Reports, 2010)
This investigation focuses on the potential in tourism interpretation of Rong Hai Community and on community members’ opinions on developing the interpretation. The population was 271 household leaders and the sample group was 170 household leaders. A self-constructed questionnaire was used to collect the data and in-depth interviews were conducted with 28 key informants consisting of formal community leaders and local intellectuals. It is found that the community has four types of tourism interpretation potential. They include knife hammering, fishing, resources in the lake, and archeological attractions. Regarding their opinions on tourism interpretation, it is found that tourists visiting the community would have experience and knowledge the most, particularly knowledge on local traditions, culture and lifestyles. Benefit from tourism interpretation is to share cultures from various localities. The most suitable interpretation method is information boards and materials used for the boards must be in line with local environment/nature as well as durable. Contents of the interpretation should be easy to understand as well as raise awareness on conservation of tourism resources.